(untitled) (Research, Society and Development, 2020)
According to the documents that are part of Basic Education, as an LDB, the Entrance to Elementary School is a discipline of teaching students. In this way, the community that is able to submit to a process capable of positioning, argue and make decisions. In Science Teaching, the ways of instigating the attitudinal knowledge enhancement, combined with conceptual knowledge, are the use of problem solving (PR). Pozo (1988) defines that PR must present situations that require students to be active and an effort to seek the true answers. Faced with such considerations and in defending the relevance of RP, it was necessary to know and map an analysis and how to use the resource in the classroom or academic research laboratories. With this objective, it was consulted as ENPEC (science teaching) and SNEF, EPEF (physics teaching). The following topics were set: to configure the use of PR in four emphases. It concludes that there is a problem with a teacher training for resource use, as well as how classroom insertions with RP are analyzed in student acceptance and performance.